2019
DOI: 10.3389/fevo.2019.00252
|View full text |Cite
|
Sign up to set email alerts
|

Wildfires Influence Abundance, Diversity, and Intraspecific and Interspecific Trait Variation of Native Bees and Flowering Plants Across Burned and Unburned Landscapes

Abstract: Wildfire regimes are changing in the western United States, yet the ways in which wildfires influence native bees, the resources they depend on for food and nesting, or the traits that influence their interactions with plants are poorly understood. In burned and unburned areas in Montana, USA, we investigated the abundance and diversity of native bees, floral and nesting resources, nesting success, and traits of flowers and bees. In two of the three localities studied, burned areas, including areas that burned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 68 publications
(96 reference statements)
1
36
0
Order By: Relevance
“…In addition to Osmia spp., bumblebees (Bombus spp.) were abundant in our study and are often among the most common taxa found at high-elevation sites 31,32 , due in part to their relatively high thermal mass in comparison to other bees 24,25,33 . Our collections provide evidence of shifts in Bombus assemblages following bark beetle outbreak: B. flavifrons was substantially more abundant in post-outbreak stands, whereas several high-elevation specialists were more frequent in non-affected stands including B. balteatus and B. melanopygus.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…In addition to Osmia spp., bumblebees (Bombus spp.) were abundant in our study and are often among the most common taxa found at high-elevation sites 31,32 , due in part to their relatively high thermal mass in comparison to other bees 24,25,33 . Our collections provide evidence of shifts in Bombus assemblages following bark beetle outbreak: B. flavifrons was substantially more abundant in post-outbreak stands, whereas several high-elevation specialists were more frequent in non-affected stands including B. balteatus and B. melanopygus.…”
Section: Discussionmentioning
confidence: 76%
“…A comparison of several recent studies and the current report reveals a growing body of evidence that both natural and managed ecosystem disturbances are important for maintaining biodiversity of native bee populations across coniferous forest landscapes. For example, complementary findings from Burkle et al 32 and Galbraith et al 20 indicate that wildfire disturbances are associated with increased diversity of multiple bee communities and across multiple conifer forest cover types. In addition to effects on taxonomic diversity, bee functional trait variation both within and between species are also responsive to these disturbances 32 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Plots were visited in random order during these hours. We considered pollinators to be any Hymenoptera (Burkle et al, 2019;Reese et al, 2018), and results were similar if we conducted all analyses using only Hymenoptera.…”
Section: Pollinator Community Samplingmentioning
confidence: 99%